Haplotypes of the IL-1 gene cluster are associated with gastroesophageal reflux disease and Barrett's esophagus - Izakovicova Holla, Lydie; Borilova Linhartova, Petra; Hrdlickova, Barbara; Marek, Filip; Dolina, Jiri; Rihak, Vladimir; Kala, Zdenek (Human immunology, 2013)
OBJECTIVES: Gastroesophageal reflux (GERD) is a one of the major public health problem that can lead to reflux esophagitis (RE), Barrett's esophagus (BE), and esophageal adenocarcinoma (EAC). The aim of our study was to determine the impact of IL-1 gene polymorphisms on the development of GERD, RE and BE. METHODS: Three hundred and thirty-three Czech patients with gastroesophageal reflux and 165 healthy controls were included in this case-control study. Four polymorphisms in the genes of the IL-1 cluster [IL-1A(-889C/T), IL-1B(-511C/T), IL-1B(+3953C/T), and IL-1RN(VNTR)] were analyzed. RESULTS: Significant differences were found in IL-1RN 1/2 genotype between patients with GERD/RE and controls and in IL-1B+3953 T allele between patients with BE and healthy subjects. In addition, complex analysis revealed differences in IL-1 haplotype frequencies between the groups. Specifically, the haplotype TCCL was significantly more frequent (p = 0.016) in GERD patients than in controls and the haplotype CCCL more frequent (p = 0.008) in RE patients than in controls. However, in patients with BE, frequency of haplotype TCTL was lower (p = 0.05) and haplotypes CTCL and TCCL were higher (p = 0.03 and p = 0.02) in comparison with the controls. CONCLUSIONS: Our results suggest that IL-1 haplotypes may be associated with susceptibility to GERD, RE and BE.
Keywords: LES; Barrettův syndrom; esophageal cancer; variable number tandem repeat; deoxyribonucleic acid; EE; Hardy–Weinberg equilibrium; genotyp; GU; Male; Gastroesophageal Reflux; DNA; Barrett’s esophagus; Genotype; interleukin-1; Česká republika; Interleukin-1; multigenová rodina; GERD; adenocarcinoma of the esophagus; Middle Aged; Haplotypes; SNP; mužské pohlaví; gastric ulcer; NERD; DU; studie případů a kontrol; linkage disequilibrium; HWE; IL-1; Adult; lower esophageal sphincter; LD; gastroezofageální reflux; Czech Republic; RE; PCR; single nucleotide polymorphism; Barrett Esophagus; gastroesophageal reflux disease; gastrointestinal quality of life index; restriction fragment length polymorphism; GIQLI; Multigene Family; gastric adenocarcinoma; EC; ženské pohlaví; non-erosive reflux disease; genetické asociační studie; zvířata; Humans; confidence intervals; GAC; odds ratio; erosive esophagitis; polymerase chain reaction; haplotypy; frekvence genu; lidé středního věku; CI; EAC; OR; Gene Frequency; reflux esophagitis; Genetic Association Studies; dospělí; BE; RFLP; VNTR; Female; duodenal ulcer; lidé; Case-Control Studies; Animals